Pharyngeal mucosal wall folds in subjects with obstructive sleep apnea - Kairaitis, Kristina; Foster, Sheryl; Amatoury, Jason; Verma, Manisha; Wheatley, John R.; Amis, Terence C. (Journal of applied physiology (1985), 2015)
Mechanical processes underlying pharyngeal closure have not been examined. We hypothesized that the pharyngeal mucosal surface would fold during closure, and lowering the upper airway lining liquid surface tension would unfold areas of mucosal apposition, i.e., folds. We compared baseline pharyngeal fold numbers and response to reduction in upper airway liquid surface tension in healthy and obstructive sleep apnea (OSA) subjects. Awake, gated magnetic resonance pharyngeal airway images of 10 healthy and 11 OSA subjects were acquired before and after exogenous surfactant administration (beractant). Upper airway liquid surface tension was measured at the beginning and end of image acquisition and averaged. Velopharyngeal and oropharyngeal images were segmented and analyzed separately for average cross-sectional area, circumference, and fold number. Compared with healthy subjects, at baseline, velopharynx for OSA subjects had a smaller cross-sectional area (98.3 ± 32.5 mm 2 healthy, 52.3 ± 23.6 mm 2 OSA) and circumference (46.5 ± 8.1 mm healthy, 30.8 ± 6.1 mm OSA; both P < 0.05, unpaired t-test), and fewer folds (4.9 ± 1.6 healthy, 3.1 ± 1.8 OSA, P < 0.03). There were no differences in oropharynx for cross-sectional area, circumference, or folds. Reduction in upper airway liquid surface tension from 61.3 ± 1.2 to 55.3 ± 1.5 mN/m ( P < 0.0001) did not change cross-sectional area or circumference for velopharynx or oropharynx in either group; however, in OSA subjects, oropharyngeal folds fell from 6.8 ± 3.1 to 4.7 ± 1.2 ( n = 8, P < 0.05), and velopharyngeal folds from 3.3 ± 1.9 to 2.3 ± 1.2 ( P = 0.08), and were unchanged in healthy subjects. Subjects with OSA have fewer velopharyngeal wall folds, which decrease further when surface tension falls. We speculate that reduced pharyngeal wall folds contribute to an increase in pharyngeal collapsibility.